Institutional Capacity Assessment for Community Rangeland Management Institutions in Pastoral Areas of Ethiopia - Eba, Bedasa; Flintan, Fiona E.; Iya, Golicha; Abdi, Hamse; Said, Mohammed (International Livestock Research Institute, 2024)
The International Livestock Research Institute (ILRI), in partnership with African Medical and Research Foundation (Amref) and Veterinaires Sans Frontiere (VSF) Suisse, are jointly implementing HEAL (One Health for Humans, Environment, Animals and Livelihood in parts of Kenya, Ethiopia and Somalia. ILRI is implementing the rangeland health component. The target is to enhance the community’s capacity for natural resource management, rangeland health and One Health through participatory rangeland management (PRM) trainings and administration of the Institutional Capacity Assessment Tool (ICAT). This is to enhance rangeland productivity and reduce threats to livestock health through organized grazing, enhance livestock mobility and restore degraded rangelands. The tool comprises a set of indicators and levels that measure the performance, governance and resilience of rangeland management institutions and can help identify strengths and weaknesses, monitor changes and provide recommendations for improvement. This document reports the ICAT for HEAL rangeland sites in Ethiopia.